2010
DOI: 10.1002/ijc.25668
|View full text |Cite
|
Sign up to set email alerts
|

Id3 modulates cellular localization of bHLH Ptf1‐p48 protein

Abstract: Ptf1-p48 is a pancreas-specific bHLH transcriptional protein, which, in the normal adult pancreas, shows a restricted expression in acinar cells where it is predominantly localized in the nucleus and activates the transcription of exocrinespecific genes. Ptf1-p48 partners with two proteins to form the PTF1 active complex: a bHLH E-protein and suppressor of hairless RBP-J. Cytoplasmic mislocalization of Ptf1-p48 has been reported in pancreatic pathologies, suggesting its contribution in the early steps of pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Several factors may explain the different observations, including variations in analytical techniques (mRNA, protein, immunostaining methods). Our Id3 immunohistological results are in agreement with a recent study of Id3 and p48 in PDA (43). …”
Section: Discussionsupporting
confidence: 93%
“…Several factors may explain the different observations, including variations in analytical techniques (mRNA, protein, immunostaining methods). Our Id3 immunohistological results are in agreement with a recent study of Id3 and p48 in PDA (43). …”
Section: Discussionsupporting
confidence: 93%
“…Dbc1 does indeed inhibit the activity of Sirt1 in the pancreas (35). Ptf1a can undergo cytoplasmic translocation in ADM (44,45), similar to what we observe for Sirt1, making a deacetylation event of Ptf1a more likely. Of note, Ptf1a might also be affected by the action of Sirt1 on pCAF that on its turn can be deacetylated by Sirt1 (46).…”
Section: Discussionsupporting
confidence: 77%
“…We and others have shown that ID3 protein levels are greatly elevated in PDA tumors. 18 20 Moreover, we showed that upregulation of ID3 is sufficient to induce cell cycle entry in quiescent human exocrine tissue. 18 High ID3, as well as attenuated expression of bHLH proteins, suggests that bHLH transcriptional networks are profoundly dysregulated in PDA and that restoring normally high bHLH activity might promote pancreatic cellular homeostasis.…”
mentioning
confidence: 87%